Cover Picture: Advanced Biofuels and Beyond: Chemistry Solutions for Propulsion and Production (Angew. Chem. Int. Ed. 20/2017). Issue 20 (21st April 2017) - Leitner, Walter; Klankermayer, Jürgen; Pischinger, Stefan; Pitsch, Heinz; Kohse‐Höinghaus, Katharina
Abstract : Following the "Fuel Design Process" To arrive at molecular structures with promising qualities for advanced future fuels, the quest for efficient catalytic production pathways based on sustainable feedstocks has to be combined with a detailed knowledge of engine combustion and emission performance. Proceeding towards this goal in "reverse" mode from tailored fuel target molecules to promising production processes is exemplified in a Review by W. Leitner, J. Klankermayer, K. Kohse‐Höinghaus et al. onpage 5412 ff. for selected routes from biomass to biofuels.